Lencz Géza és a vármegyei alap - Király, Sándor (Gerundium, 2014)
GÉZA LENCZ AND THE COUNTY FOUNDATION. Géza Lencz is mostly remebered as a theology professor who was a determinant personality in the early history of the University and a legendary teacher of the Calvinist heology Faculty. It is not widely known about him that during his rectorship, while he was persistently fought for the main university building being built, a foundation was established, to support the construction work, collecting the donation of the counties for this noble cause. he county foundation, which was clearly his idea and for which he has sacriied so much, could not fulill its purpose, however it became an eicient support system for the deserving needy students.